Characteristics of Position and Team Work with Employee Performance at the Public Works and Public Housing Office of Bogor Regency - Usmar Ismail; Sismiati Sismiati; Syarifuddin Sulaiman (Serat Acitya, 2022)
The purpose of this study was to analyze and test the influence of position characteristics and team work on employee performance. This research was conducted at the Office of the Public Works & Public Housing Agency, Bogor Regency, West Java. The population in this study were all employees with the status of State Civil Apparatus (ASN) at the Bogor District Public Works & Public Housing Service. The population in this study were 287 people. By using the Slovin formula, a total sample of 167 people was obtained. The analysis technique used is multiple regression analysis. The results of the analysis show that job characteristics and team work have a significant effect on employee performance.